Kinetic evaluation of influencing factors on the composition of a Fe–Al–Mn–C steel and mold flux during continuous casting - Rongzhen Mo; Chihao Zhang; Ying Ren; Lifeng Zhang (Journal of Materials Research and Technology)
The influence of the temperature, casting speed, mold flux consumption rate, molten pool depth, initial Al content, and initial Al2O3/SiO2 ratio on the continuous casting of the Fe–Al–Mn–C steel was discussed by the kinetic model. The kinetic model for the continuous casting of the Fe–Al–Mn–C steel was validated through experimental results involving mold fluxes of reactive, low-reactive, and non-reactive. It was found the equilibrium time increased from 309 to 1786 s with the increase of the molten pool depth. The equilibrium time significantly reduced from 1145 to 826 s when the mold flux consumption rate increased. The increase of the casting speed resulted in the significantly decrease of the equilibrium time from 1226 to 736 s. The casting time required to reach equilibrium first increased from 916 to 1417 s and then decreased from 1417 s to 906 s as the initial Al content rose from 0.10 wt% to 0.75 wt%, while the maximum Al2O3 accumulation rate increased. When the initial Al content exceeded 1.5 wt%, it hardly influenced the maximum Al2O3 accumulation rate and equilibrium time. A higher initial Al2O3/SiO2 ratio alleviated the Al2O3 accumulation in the mold flux due to a faster equilibrium time and a slower maximum Al2O3 accumulation rate.